Conhecimento do professor sobre dificuldades de aprendizagem no tópico adição de expressões algébricas no Ensino MédioTeachers’ knowledge on students learning difficulties in the topic of addition of algebraic expressions in upper secondary - Sosa, Leticia; Guzmán Castro, Marlene Vianney; Ribeiro, Miguel (Educação Matemática Pesquisa: Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2019)
El objetivo de esta investigación es caracterizar el conocimiento de dos profesoras de matemáticas en formación continua, sobre dificultades de aprendizaje de los alumnos inherentes al contenido matemático de suma de expresiones algebraicas. Ese conocimiento se analiza al planificar, ejecutar y hacer la propuesta de mejora en el tema de adición de expresiones algebraicas para segundo grado de educación secundaria, utilizando el modelo Mathematical Teacher Specialised Knowledge como herramienta teórica y analítica. La investigación consiste de un estudio de caso instrumental a partir de la observación no participante y los resultados muestran el conocimiento de las profesoras sobre las dificultades de aprendizaje de los alumnos en el tema de adición de expresiones algebraicas, dando tratamiento desde la planificación. This research aims at characterize the knowledge of two mathematics teachers participating in a professional development context, on the students learning difficulties inherent to the addition of algebraic expressions. Such knowledge is analysed when put in action to plan, execute and make suggestions for improvement of their practice in the topic of adding algebraic expressions in upper secondary and for such analysis the Mathematical Teachers Specialised Knowledge is assumed as a theoretical and analytical tool. An instrumental case study with a non-participant observation has been carried and the results pinpoint the teachers knowledge about the students learning difficulties of and for adding algebraic expressions, taking that into consideration since planning.